Iliac venous stenting as adjunct in the management of symptomatic orthostatic hypotension in iliac vein compression - Andres V. Figueroa, MD; Sebastian Cifuentes, MD; Jorge H. Ulloa, MD; Joseph Raffetto, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Orthostatic hypotension (OH) is a common cardiovascular disorder with high prevalence in the elderly. Concomitant venous return impairment may worsen the autonomic response and accentuate the symptoms. We detailed a patient with severe OH, prominent varicosities, and hemosiderin deposition in lower limbs. After excluding autonomic and neurological etiology, a computed tomography venography revealed significant common iliac vein compression. The patient was deemed to benefit from venous stenting. At a 2-year follow-up, the patient reported symptom improvement with adequate stent patency. Venous stenting may aid in the treatment of patients with severe OH symptoms without clear etiology and impairment of venous return.